Cost-effectiveness of EGCRISC application versus hepatitis C virus mass screening in Egypt - Engy M. El-Ghitany (Elsevier, 2019)
Background: The Egyptian model of care against hepatitis C virus (HCV) has a great success in treatment and treatment accessibility, but still screening efforts must be strengthened. HCV is a silent infection when most of infected people are unaware of their infection. EGCRISC is a newly developed and validated risk-based HCV screening tool in Egypt that has shown a considerably good performance but is still underused. This brief communication is to analyze its use cost-effectiveness versus mass screening. Study design: Mathematical comparative analysis for economic evaluation. Methods: Its performance data as published recently were used, and a minimum cost of L.E. 20 was considered per one antibody testing. The 2015 health issue survey and population census were used for estimating the population, infected individuals and susceptibles. Results: The analysis showed that using EGCRISC would save LE 0.43 billion accounting for about 21,646,227 unnecessary tests, while missing less than 70,000 cases when compared to mass screening. Conclusion: EGCRISC is a cost-effective tool that must be adopted nationwide as soon as possible in Egypt for the best outcome of HCV control. Keywords: HCV, EGCRISC, Cost-effectiveness, Screening